Causes of corruption: history, geography and government - Rajeev K. Goel; Michael A. Nelson (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
Corruption, which remains a serious problem in many countries, has prompted considerable research in recent years. This paper adds to the extant literature with insights on factors influencing corrupt activity. Using cross-country data for about 100 nations, the roles of national history, geography, and government are examined to see how they affect conditions for corruption, both qualitatively and quantitatively. The innovative aspects of this research include use of a wide set of historical, geographical, and governmental determinants of corruption, as well as detailed assessment of several previously considered determinants. The main issues addressed are the effects of the size and scope of government on the incidence of corruption across countries, and the significance of historical and geographic factors in corruption. Regarding the first question, the authors find the size and scope of government can significantly affect corruption. On the second, it is shown that historical institutional inertia in older countries and new rent-seeking opportunities in younger nations can encourage corruption, while certain geographic factors can mitigate corruption. The paper ends with discussion aimed at the policymaker.
URN:NBN:fi:bof-201408071925
Keywords: H0; P0; 330; corruption; bribery; government size; government scope; rent-seeking; history; geography